Distribusi Keganasan Organ Tiroid Berdasarkan Pemeriksaan Histopatologi di Kota Pekanbaru - Wiwit Ade Fidiawaty; Selvialiany Selvialiany; Welly Zulfikar (Fakultas Kedokteran Universitas Riau, 2016)
Cancer is one of the leading causes of death. Cancer can occur in various organs of the human body. Thyroid canceris one of the most common cancer. Pathological based registration indicates that thyroid cancer is the ninth of theoverall cancer and the most common type of endocrine related cancer. The purpose of this research was to determinethe distribution of thyroid cancer in Pekanbaru’s Hospital during 2009-2013 based on histopathologic type, age andgender. This research was a retrospective study were retrieved based on result of hospital’s histopathology laboratoriesand histopathology laboratories centers in Pekanbaru. The results showed 163 cases of thyroid cancer. Mostly foundat RSUD Arifin Achmad Riau Province as many as 106 cases (65%). The cancer was dominated by women (83,4%).The age range of most thyroid cancer is 35-44 years (24,5%). The most common histopathological type of thyroidcancer was papillary thyroid cancer, as many as 111 cases (68,1%).